Analisis Beban Kerja Mental Menggunakan Metode Nasa-Tlx: Studi Kasus Pada Service Engineering PT. Xyz - Widyani, Sulthan Fathoni (Jurnal Ilmiah Wahana Pendidikan, 2024)
Human resources (HR) are a determining factor for success in achieving a company's goals. Excessive workload can have a serious impact on various aspects of life. Therefore, the aim of implementing the NASA-TLX method is to increase employee work efficiency and productivity, as well as minimize the risk of fatigue and stress which can affect employee health and performance. The research methodology used in this research is the research and development method, which refers to identifying problems in the field and carrying out development. Based on the recapitulation results of PT workers' WWL calculations. XYZ is 81.165 which is included in the very high category. Of the 8 respondents who filled out the questionnaire, it was found that the results of the interpretation of employees' mental workload were 4 workers who got very high interpretation scores and 4 workers who got high interpretation scores. If the company wants to reduce the mental workload and efforts made in the Service Engineering section, remember if there are additional employees, it will cost the company more, with the addition of 1 worker reducing the workload and mental load from 81,165 to 72.15, the addition of 2 workers to 64.93 and the addition of 3 workers to 59.02.